2014
DOI: 10.1021/jf501578w
|View full text |Cite
|
Sign up to set email alerts
|

Lentinan Degradation in the Lentinula edodes Fruiting Body during Postharvest Preservation Is Reduced by Downregulation of the exo-β-1,3-Glucanase EXG2

Abstract: Lentinan from Lentinula edodes fruiting bodies (shiitake mushrooms) is a valuable β-glucan for medical purposes based on its anticancer activity and immunomodulating activity. However, lentinan content in fruiting bodies decreases after harvesting and storage due to an increase in glucanase activity. In this study, we downregulated the expression of an exo-β-1,3-glucanase, exg2, in L. edodes using RNA interference. In the wild-type strain, β-1,3-glucanase activity in fruiting bodies remarkably increased after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Lentinula edodes has three GH55 family exo-␤-1,3-glucanases that are mostly conserved in filamentous fungi and also exist in several bacteria (39). EXG2, a member of the GH55 family which is involved in cell wall degradation after harvest (27), has a strong effect on lentinan degradation after harvest (40). The enzyme encoded by exg2 in the GH55 family of exo-␤-1,3-glucanases was not determined to be a DEG, but its expression was upregulated more than 15-fold in the fruiting body after harvest (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lentinula edodes has three GH55 family exo-␤-1,3-glucanases that are mostly conserved in filamentous fungi and also exist in several bacteria (39). EXG2, a member of the GH55 family which is involved in cell wall degradation after harvest (27), has a strong effect on lentinan degradation after harvest (40). The enzyme encoded by exg2 in the GH55 family of exo-␤-1,3-glucanases was not determined to be a DEG, but its expression was upregulated more than 15-fold in the fruiting body after harvest (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…2). RNA interference tools are available in Lentinula edodes (40,73), and TILLING, a method for screening mutants that have a mutation in a target gene (74), will be applicable for breeding. Gene expression for wood decay, biofilm formation in sawdust, medium cultivation, and fruiting body primordia in Lentinula edodes has been reported.…”
Section: Resultsmentioning
confidence: 99%
“…31 On the content of dried shiitake Table 1. Effects of intensive pulsed light (IPL) and hot water blanching (HB) pretreatments on shiitake mushroom polysaccharides (SMPs), 5-hydroxymethylfurfural (5-HMF), reducing sugars content (RSC), total phenolic content (TPC), surface color, browning index (BI) and browning degree (BD) of dried shiitake mushrooms 32 However, the range of dried SMPs pretreated with HB decreases by 17.65% compared with the untreated sample. Polysaccharides might engender this decline because of their high solubility in water (after blanching pretreatment) and because of non-enzymatic browning, which started at higher temperatures.…”
Section: Influence Of Pretreatment On Non-enzymatic Browningmentioning
confidence: 99%
“…The Rho1‐Mpk1 cascade is involved in cell wall biosynthesis in various fungi (Kwon et al ., 2010; Lam et al ., 2013); thus, it is possible that some of the GH/AA‐encoding genes upregulated in the ccl1 disruptants and the rho1b OE strains are involved in cell wall biosynthesis, but not in cellulose degradation. Various studies have suggested that cell wall biosynthesis/remodelling may be related to fruiting body development in some agaricomycetes (Kamada et al ., 1991; Muraguchi and Kamada, 2000; Tao et al ., 2013; Konno et al ., 2014; Zhou et al ., 2019); therefore, we analysed the effects of rho1b or mpk1b disruption on fruiting development to examine this possibility.…”
Section: Resultsmentioning
confidence: 99%